2021
DOI: 10.3389/fncel.2021.632354
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Acyl-CoA Synthetase Long-Chain Family Member 4 Facilitates Neurological Recovery After Stroke by Regulation Ferroptosis

Abstract: BackgroundIschemic stroke is the main cause of disability worldwide, leading to a serious socioeconomic burden. Ferroptosis is a non-apoptotic form of programmed cell death and is related to various diseases. Acyl-CoA synthetase long-chain family member 4 (ACSL4) is considered a target of ferroptosis, but its specific role in ischemic stroke remains unclear. In this study, we investigate whether the inhibition of ACSL4 promotes the recovery of neurological function in a way that prevents ferroptosis.MethodsA t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 37 publications
3
54
0
Order By: Relevance
“…Iron deposition occurs in the basal ganglia, thalamus, periventricular, and subcortical white matter areas during the brain injury caused by severe ischemia [ 76 ]. In mouse models of ischemic stroke, the GSH content and GPX4 activity decreased in the neuronal cell, and lipid peroxide production increased [ 77 ], indicating that ferroptosis is the main form of neuronal death after ischemic stroke.…”
Section: Ferroptosis In Neurological Diseasesmentioning
confidence: 99%
“…Iron deposition occurs in the basal ganglia, thalamus, periventricular, and subcortical white matter areas during the brain injury caused by severe ischemia [ 76 ]. In mouse models of ischemic stroke, the GSH content and GPX4 activity decreased in the neuronal cell, and lipid peroxide production increased [ 77 ], indicating that ferroptosis is the main form of neuronal death after ischemic stroke.…”
Section: Ferroptosis In Neurological Diseasesmentioning
confidence: 99%
“…Ferritin reduces robust ROS production and GSH consumption; its decrease is necessary for cerebral ischemia-induced hippocampal neuronal ferroptosis through p53 and SLC7A11 in middle cerebral artery occlusion (MCAO) rats ( Chen W. et al, 2021 ), and mice lacking mitochondrial ferritin show graver brain injury and neurological deficits, accompanied by typical ferroptotic event after cerebral ischemia/reperfusion (I/R) ( Wang et al, 2021 ). ACSL4 enhances ischemic stroke by increasing ferroptosis-induced brain damage and neuroinflammation while inhibiting ACSL4, which promotes the recovery of neurological function following stroke ( Li et al, 2019 ; Chen J. et al, 2021 ; Cui et al, 2021 ). Tuo et al ( 2017 ) demonstrated that tau suppression reduces MCAO-induced ferroptosis and influences ischemic stroke outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The level of lncRNA-PVT1 is upregulated and the miR-214 level is downregulated in the plasma of acute ischemic stroke patients, and PVT1 involves ferroptosis via miR-214-mediated TFR1 and TP53 levels in brain I/R ( Lu et al, 2020 ). By the bioinformatic analysis, three ferroptosis-related biomarkers are found as potential diagnostic biomarkers for ischemic stroke, namely, PTGS2, MAP1LC3B, and TLR4, which are upregulated in ischemic stroke and provide more evidence about the important role of ferroptosis ( Chen G. et al, 2021 ). Therefore, extensive evidence suggests that ferroptosis is one of the key pathological mechanisms of nerve injury and neurological dysfunction after stroke, which is a potentially promising therapeutic target ( Jin Y. et al, 2021 ; Li Y. et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic screenings conducted throughout the entire genome later identified an enzyme called acyl-CoA synthetase long-chain family member 4 (ACSL4), which was used to measure the susceptibility of cells to ferroptosis after being discovered by accident [ 28 ]. Activation of long-chain polyunsaturated fatty acids (PUFAs) is thought to have a role in ferroptosis because these PUFAs may enhance the likelihood of the formation of lipid peroxidation when they are included in phospholipids [ 29 ].…”
Section: Mechanism Of Ferroptosismentioning
confidence: 99%